2016
DOI: 10.1016/j.neuropharm.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

The mood stabilizer valproic acid opposes the effects of dopamine on circadian rhythms

Abstract: a b s t r a c tEndogenous circadian (~24 h) clocks regulate key physiological and cognitive processes via rhythmic expression of clock genes. The main circadian pacemaker is the hypothalamic suprachiasmatic nucleus (SCN). Mood disorders, including bipolar disorder (BD), are commonly associated with disturbed circadian rhythms. Dopamine (DA) contributes to mania in BD and has direct impact on clock gene expression. Therefore, we hypothesized that high levels of DA during episodes of mania contribute to disturbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…Indeed, our results showed a 2-h shift in the circadian rhythm of the VPA group. In parallel with our result, an earlier report showed that VPA shortened circadian period in vivo and in vitro and suppressed behavioral activity across species (Landgraf et al, 2016). ASD patients often have sleep problems and altered social timing, and it has been correlated with identified single nucleotide polymorphisms (SNPs) of Per1 and Npas2 genes (Nicholas et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, our results showed a 2-h shift in the circadian rhythm of the VPA group. In parallel with our result, an earlier report showed that VPA shortened circadian period in vivo and in vitro and suppressed behavioral activity across species (Landgraf et al, 2016). ASD patients often have sleep problems and altered social timing, and it has been correlated with identified single nucleotide polymorphisms (SNPs) of Per1 and Npas2 genes (Nicholas et al, 2007).…”
Section: Discussionsupporting
confidence: 89%
“…These changes in period may facilitate phase shifting, improve entrainment and have important implications for lithium's effects on mood. In the dopamine transporter (DAT) knockdown model of mania, mice have a longer circadian period, and the period was shortened by the mood stabilizer valproic acid [33]. Similar period shortening effects of valproic acid were observed in gene expression rhythms in cells from BD patients [33], an effect on rhythms similar to selective GSK3 inhibitors [32].…”
Section: Introductionmentioning
confidence: 73%
“…86 These components of the dopamine signaling network provide inputs into the circadian clock. Indeed, we have shown previously that D1R modulate circadian period length in SCN slices from PER2::LUC mice, 88 while others demonstrated that D2Rs and D3Rs affect modulation of the CLOCK/BMAL1 dimerization in the retina. 89 Moreover, the same dopamine receptors determine the time of peak PER2 expression in the striatum.…”
Section: Reciprocal Links Between Dopamine Signaling and The Circadiamentioning
confidence: 81%